Revisit of the Association between Cytomegalovirus Infection and Invasive Fungal Infection after Allogeneic Hematopoietic Stem Cell Transplantation: A Real-World Analysis from a High CMV Seroprevalence Area - Tsung-Jang Yeh (Journal of Fungi, 2022)
Infection is a major complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT) especially cytomegalovirus (CMV) infection and invasive fungal infection (IFI). Taiwan is a high CMV seroprevalence area. Our study aimed to evaluate the incidence, risk factors, the impact on survival of CMV infection (including reactivation and disease) and the association of CMV infection and IFI in recipients after allo-HSCT during the first 100 days after transplantation. This was a retrospective study including 180 recipients of allo-HSCT. A total of 99 patients had CMV reactivation, and nine patients had CMV diseases. There were more mismatched donors, more ATG usage and more transplantation from CMV IgG-negative donor in patients with CMV reactivation. There was no survival difference in patients with or without CMV reactivation. A total of 34 patients had IFIs, and IFI after allo-HSCT was associated with significantly inferior survival. Patients with CMV reactivation did not increase the incidence of overall IFI, but they did result in more late-onset (>40 days) IFI (p = 0.056). In this study, we demonstrated real-world data of CMV infection and IFI from a high CMV seroprevalence area.